Tribology in Total Hip Arthroplasty - Knahr, Karl (Springer Berlin Heidelberg : Imprint: Springer, 2011)
During the 2010 EFORT Congress in Madrid, many interesting topics relating to tribology in total hip arthroplasty were discussed during a special day devoted entirely to the subject. So successful was the day, and such was the broad interest in the discussions, that EFORT decided that publication of all the presentations would be warmly welcomed by fellow professionals who were unable to attend. This book is the result. It includes detailed information on the different articulating materials and the wear to which they are subject. The various factors that contribute to bearing performance and control wear are thoroughly evaluated, and careful consideration is given to the technology and design solutions proposed with a view to producing low-wearing hip joints. This book will be of interest both to novices who want to learn more about the field and to experienced orthopaedic surgeons wishing to keep abreast of the latest developments.